O construtivismo moral e político de Jonh Rawls e a relação com a ética kantiana - Cagnini, Valdinei (2020)
Justice is the first virtue of social institutions, as is truth of thought systems. Although elegant and economical, a theory must be rejected or revised if it is not true; likewise, laws and institutions, however efficient and well organized, must be reformed or abolished if they are unjust. (RAWLS, 2000, p. 3-4). Nowadays, from the ethical and political field, the term constructivism is linked to John Rawls with the publication of the work A Theory of Justice (1971). Constructivism is characterized by a search for principles able to organize the society and at the same time being accepted by all. These principles serve precisely as the basic structure of political institutions, they operate as the originators of subsequent agreements. That is, the principles will be able to order the basic structures of a society, when submitted in a specific situation called by Rawls an "original position", submitted to restrictive questions, by the "veil of ignorance”. For Rawls, people are more interested in themselves than in others. The function of the veil of ignorance is a mechanism introduced by Rawls, in order to avoid that social, natural contingencies, the result of chance, distort the distributive results. Therefore, the idea of the original position is to establish a fair process, so that any accepted principles are fair. The purpose of the veil of ignorance is to deprive any particular choice. For constructivism, the principle of justice is the result of a construction process. The presupposed idea is the recognition of rational and reasonable individuals (faculties), who are able to formulate, respectively, a conception of the good and to develop a sense of justice. From the moral point of view, the interlocutor that best presents compatibility with Rawls' thought is Immanuel Kant, who proposes a comprehensive moral doctrine, in which the idea of autonomy is regulating the political and moral world. For Kant, autonomy is conditional on obedience to universally valid moral principles, in accordance with the categorical imperative: “Act only according to the maxim you can at the same time want it to become a universal law” (FMC. 2007. p 69).What distinguishes the Kantian version of constructivism is essentially that it proposes a particular conception of the person and that makes it an element of a reasonable construction procedure whose result determines the content of the first principles of justice.